Adaptation Program of Reading Learning for Dyslexic Students in Elementary Schools - Tjutju Soendari; Tati Hernawati; E. Ehan (Jurnal Dedikasi, 2020)
Learning implementation is a frequent problem faced by inclusive education teachers in elementary schools. It becomes more difficult by the fact that there are still many dyslexic students incapable of reading a sentence or even a word. Meanwhile, teachers are still applying the same learning program for both average students and students with disabilities. To archive this, we encode an adaptation program which aims to provide training and mentoring to elementary school teachers. In this study, we conduct the research in SD Mandiri 2 Cibabat, City of Cimahi. The activities include zoom meeting discussing about the basic concept of dyslexic students, the reading method for dyslexic students, and the basic concepts of adaptation program of reading learning for dyslexic students. Then, it is followed by mentoring on reading skill assessment, workshop analysis, forming the adaptation program, and training the implementation. The result of the study is in the form of guided learning on implementing the adaptation of reading learning for dyslexic students, which expectedly accommodates and improves the students’ reading ability.